Electrochemical Chiral Recognition at Molecular Imprinting Au Surfaces. Issue 13 (16th August 2019) - Niu, Xiaohui; Yang, Xing; Mo, Zunli; Pan, Zhao; Liu, Zhenyu; Shuai, Chao; Gao, Qinqin; Liu, Nijuan; Guo, Ruibin
Abstract : Electrochemical chiral sensing platform based on a novel molecularly imprinted metal was constructed in the presence of polypyrrole (PPy) and tryptophan (Trp) enantiomers. The chiral microenvironment was preserved on the chirally imprinted Au after removing the template molecules, which was then used for the electrochemical recognition of Trp enantiomers. The enantiomeric selectivity were 2.788 and 3.186 for L and D-Trp imprinted Au surface, respectively. The sensing matrix had a linear range of 0.01 mM to 13 mM with a LOD of 0.012 μM and 0.009 μM for L and D-Trp. The sensor was also used to detect D or L-Trp in real samples.